CDK 4/6 Inhibitors as Single Agent in Advanced Solid Tumors - Schettini, Francesco; De Santo, Irene; Rea, Carmen G.; De Placido, Pietro; Formisano, Luigi; Giuliano, Mario; Arpino, Grazia; De Laurentiis, Michelino; Puglisi, Fabio; De Placido, Sabino; Del Mastro, Lucia (Frontiers in Oncology, 2018)
Cyclin-dependent kinases (CDK) 4/6 inhibitors, namely abemaciclib, palbociclib and ribociclib, interfere with cell cycle progression, induce cell senescence and might promote cancer cell disruption by a cytotoxic T cells-mediated effect. Phase III randomized clinical trials have proven that CDK4/6 inhibitors (CDK4/6i) in combination with several endocrine agents improve treatment efficacy over endocrine agents alone for hormone receptor positive (HR+) HER2 negative (HER2-) metastatic breast cancer (MBC). Based on such results, these combinations have been approved for clinical use. Preclinical studies in cell cultures and mouse models proved that CDK4/6i are active against a broad spectrum of solid tumors other than breast cancer, including liposarcoma, rhabdomyosarcoma, non-small cell lung cancer, glioblastoma multiforme, esophageal cancer and melanoma. The role of CDK4/6i in monotherapy in several solid tumors is currently under evaluation in phase I, II and III trials. Nowadays, abemaciclib is the only of the three inhibitors that has received approval as single agent therapy for pretreated HR+ HER2- MBC. Here we review biological, preclinical and clinical data on the role of CDK4/6 inhibitors as single agents in advanced solid tumors.